Building Sustainable Hybrid Organizations: The Case of Commercial Microfinance Organizations - Battilana, Julie; Dorado, Silvia (Academy of Management Journal, 2010)
We explore how new types of hybrid organizations (organizations that combine institutional logics in unprecedented ways) can develop and maintain their hybrid nature in the absence of a “ready-to-wear” model for handling the tensions between the logics they combine. The results of our comparative study of two pioneering commercial microfinance organizations suggest that to be sustainable, new types of hybrid organizations need to create a common organizational identity that strikes a balance between the logics they combine. Our evidence further suggests that the crucial early levers for developing such an organizational identity among organization members are hiring and socialization policies.